Koronivia grass (Urochloa humidicola) interference on nutrient content and accumulation of maize aerial part (Research, Society and Development, 2025)
The maize-Urochloa intercropping is used to recovery degraded pastures and straw formation and soil cover in a no-tillage system, providing financial and environmental benefits. However, the forage can negatively impact the crop through competition for nutrients and can impair corn crop performance, thus compromising the success of the intercrop. Thus, the objective was to estimate the interference of koronivia grass (Urochloa humidicola), BRS Tupi, in maize (Zea mays), BRS Saracura, by quantifying the maize aerial dry mass matter (MADMM) and the nutrient (nitrogen, phosphorus, potassium, calcium, magnesium and sulfur) contents and accumulations in the MADMM. The experiment was conducted in a greenhouse in a completely randomized design with four replicates, with treatments consisting of five different infestation densities of koronivia grass: zero, one, two, three, and four plants/pot. Increasing infestation density significantly reduced MADMM, nitrogen, potassium, magnesium, and sulfur contents, and all macronutrientes accumulation. Phosphorus and calcium levels in MADMM were not affected by koronivia grass interference.